2021
DOI: 10.1108/jkm-03-2021-0185
|View full text |Cite
|
Sign up to set email alerts
|

How and when do employees hide knowledge from co-workers?

Abstract: Purpose Drawing on social learning and social cognitive theories, this study aims to examine a multi-level moderated mediation model that tests the mediating effect of moral disengagement (MD: Level 1) between perceived organisational politics (POP: Level 1) and employee knowledge hiding from coworkers (EKHC: Level 1). The authors further propose that supervisor knowledge hiding from employees (SKHE: Level 2) moderates this mediation effect. Design/methodology/approach The authors obtained multi-sourced, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…The results support and find POQ has a positive and significant relationship with knowledge hiding. Previous studies show that employees’ negative feelings such as injustice (Erdogan et al , 2020b) and relative deprivation (Connelly et al , 2019) are intensified by perceived overqualification, leading to an increase in knowledge hiding behaviour (Strik et al , 2021; Koay and Lim, 2021; Arain et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results support and find POQ has a positive and significant relationship with knowledge hiding. Previous studies show that employees’ negative feelings such as injustice (Erdogan et al , 2020b) and relative deprivation (Connelly et al , 2019) are intensified by perceived overqualification, leading to an increase in knowledge hiding behaviour (Strik et al , 2021; Koay and Lim, 2021; Arain et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to equity theory when employees feel that they are not treated according to their qualification they experience negative feelings such as injustice (Zhao et al, 2021;Erdogan et al, 2020b) and relative deprivation (Connelly et al, 2019) are intensified by perceived overqualification, leading to an increase in knowledge hiding behaviour (Strik et al, 2021;Koay and Lim, 2021;Arain et al, 2021). POQ may also restrict an individual's immediate thinking action system, limiting their freedom of thought and action (Li et al, 2021), leading employees to hide knowledge from the knowledge requester.…”
Section: Perceived Overqualification and Knowledge Hidingmentioning
confidence: 99%
“…For instance, ESM usage induces psychological transition and information overload (Chen and Karahanna, 2018), as well as ESM-related exhaustion (Luqman et al, 2021). Importantly, despite ESM's positive outcomes, it also induces negative psychological outcomes, which hinder employees' productivity and trigger harmful behaviours, such as knowledge hiding (Ma et al, 2020;Arain et al, 2022Arain et al, , 2021. Therefore, it is not sufficient to study the positive or negative effects of ESM on employee performance in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…First, the impact of power on knowledge sharing is an underexplored area across the entire spectrum of the knowledge sharing literature. A few studies provide preliminary indications that higher-status employees are more likely to share knowledge than are lower-status employees (Harari et al , 2021; Arain et al , 2021). Some authors have also suggested that employees who are afraid of losing their unique status are less likely to participate in knowledge sharing (Ardichvili et al , 2006), while employees who wish to enhance their status are more likely to participate in such activities (da Silva et al , 2022).…”
Section: Introductionmentioning
confidence: 99%